Використання чорниць у щоденному й обрядовому харчуванні населення Правобережного Полісся: кашоподібні страви, узвари, киселі, настоянки - Дмитренко, А. (Матеріали до української етнології, 2019)
У статті йдеться про ягоди чорниці в системі традиційного щоденного, святкового й обрядового харчування мешканців Правобережного Полісся та зміни, що відбулися в останні десятиліття. З’ясовано місце свіжих (сирих) чорниць у раціоні в період ягідного сезону; показано способи їх заготівлі на запас; висвітлено особливості приготування кашоподібних страв із сухих і свіжих чорниць та подано їхні локальні назви; розглянуто використання цих ягід для узварів, киселів і настоянок; визначено місце страв із чорниць у системі харчування в період постів та свят. Для ілюстрації основних положень статті наведено польові матеріали. The article is dedicated to the traditions of calendar regulation of bilberry harvesting in the Right-Bank Polissia and the changes that have taken place in recent decades. The investigation is based on field ethnographic materials recorded during historical and ethnographic expeditions (2005–2014), organized by the State Scientific Center for the Protection of Cultural Heritage from Technological Disasters and the Museum of Ethnography of Volhynia and Polissia at the Lesia Ukrayinka East European National University. Traditions that have been developed in the system of calendar regulation of bilberry picking in the Right-Bank Polissia and the changes caused by the mass harvesting of these berries in recent decades are described. It is noted that the terms of bilberry harvesting are extremely blurred, which is caused primarily by the biological characteristics of this berry. It has a long vegetative period and is kept well, so it can be harvested from late summer to the next year's spring. In some places, the beginning of bilberry picking is associated with the other plants' development (reaching the viburnum).